1992
DOI: 10.1083/jcb.119.6.1573
|View full text |Cite
|
Sign up to set email alerts
|

Zyxin and cCRP: two interactive LIM domain proteins associated with the cytoskeleton.

Abstract: Abstract. Interaction with extraceUular matrix can trigger a variety of responses by cells including changes in specific gene expression and cell differentiation. The mechanism by which cell surface events are coupled to the transcriptional machinery is not understood, however, proteins localized at sites of cell-substratum contact are likely to function as signal transducers. We have recently purified and characterized a low abundance adhesion plaque protein called zyxin (Crawford, A. W., and M. C. Beckerle.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
247
0
2

Year Published

1996
1996
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(257 citation statements)
references
References 114 publications
7
247
0
2
Order By: Relevance
“…Paxillin binds to cytoskeletal component proteins, such as vinculin, talin and pp125 FAK , and zyxin binds to a-actinin, through the regions outside of the LIM domains Turner and Miller, 1994;Salgia et al, 1995), while zyxin and CRP are associated with each other through LIM ± LIM interactions (Sadler et al, 1992;Schmeichel and Beckerle, 1994). As the LIM domains are thought to function as the interface in proteinprotein interactions, the LIM domains of cytoskeletal LIM proteins are likely involved in their binding to cytoskeletal component proteins or regulatory proteins, and thus may contribute to the regulation of cytoskeletal reorganization.…”
Section: Discussionmentioning
confidence: 99%
“…Paxillin binds to cytoskeletal component proteins, such as vinculin, talin and pp125 FAK , and zyxin binds to a-actinin, through the regions outside of the LIM domains Turner and Miller, 1994;Salgia et al, 1995), while zyxin and CRP are associated with each other through LIM ± LIM interactions (Sadler et al, 1992;Schmeichel and Beckerle, 1994). As the LIM domains are thought to function as the interface in proteinprotein interactions, the LIM domains of cytoskeletal LIM proteins are likely involved in their binding to cytoskeletal component proteins or regulatory proteins, and thus may contribute to the regulation of cytoskeletal reorganization.…”
Section: Discussionmentioning
confidence: 99%
“…Although the zinc-finger motif had originally been thought of as a DNA binding domain, more recent evidence suggests that it also facilitates protein-protein interactions (Sehmeichel and Beekerle, 1994). The LIM domain, for example, occurs in a variety of proteins with diverse functions and subcellular distributions, including transcription factors, protooncogene products, components of adhesion plaques, and the actin-based cytoskeleton (Sadler et al, 1992;Crawford et al, 1994). In a similar manner, the members of the RING-finger family have been reported to function as transforming agents, as facilitators of protein-protein interactions (Freemont, 1993), and as regulators of development and cell differentiation (Cheng et al, 1995;Yoon et al, 1995).…”
Section: Figmentioning
confidence: 99%
“…LIM domain proteins have been implicated in developmental regulation, cellular differentiation, and actin-based cytoskeletal interaction (Sadler et al 1992;Crawford et al 1994;Sanchez-Garcia and Rabbitts 1994). Spectroscopic studies of LIM domains derived from a number of different proteins have revealed that the LIM domain specifically coordinates two zinc ions (Michelsen et al 1993Archer et al 1994;Kosa et al 1994).…”
Section: Introductionmentioning
confidence: 99%